The Influence of Youth in Regional Development Through the Management of Aceh's Special Autonomy Fund in Langsa City - M Irvanni Bahri; Sirojuzilam Sirojuzilam Sirojuzilam; Rujiman Rujiman Rujiman; Early Ridho Kismawadi (E-Mabis: Jurnal Ekonomi Manajemen dan Bisnis, 2021)
This research aims to determine the contribution of youth in regional development through the management of special autonomy funds in Langsa City, then to find out the factors that encourage and hinder youth in the development of the region through the management of special autonomy funds in Langsa City.  The method used in this research is quantitative method by looking at the influence of youth in regional development through the management of special autonomy funds in Langsa City, this research was conducted in Langsa City by testing hypotheses and explaining and identifying causal relationships between various variables.   The population in this study was 22,916 youth people age range from 16 - 30 years, so the percentage of leeway used is 10 % and the calculation results using slovin formula can be rounded to 100 people as a sample. The results of youth research in Langsa City have a significant influence in the development of the region through the management of special autonomy funds.